2020
DOI: 10.1136/gutjnl-2020-321191
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of psychological therapies for irritable bowel syndrome: systematic review and network meta-analysis

Abstract: ObjectivesNational guidelines for the management of irritable bowel syndrome (IBS) recommend that psychological therapies should be considered, but their relative efficacy is unknown, because there have been few head-to-head trials. We performed a systematic review and network meta-analysis to try to resolve this uncertainty.DesignWe searched the medical literature through January 2020 for randomised contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
139
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 105 publications
1
139
0
4
Order By: Relevance
“…85 In a recent meta-analysis based upon 11 European datasets, 14 containing over 2700 patients, the total annual cost related to IBS was estimated at almost €3000 per patient. Although therapies for IBS with proven efficacy exist, [86][87][88][89][90] none are curative, and their cost-effectiveness remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…85 In a recent meta-analysis based upon 11 European datasets, 14 containing over 2700 patients, the total annual cost related to IBS was estimated at almost €3000 per patient. Although therapies for IBS with proven efficacy exist, [86][87][88][89][90] none are curative, and their cost-effectiveness remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…To inform this guideline, we updated a series of systematic reviews and trial-based or network meta-analyses conducted by some of the authors. [153][154][155][156][157][158][159][160][161][162][163] The aim was to assess the efficacy of dietary modifications and therapies, unlicensed, as well as licensed, pharmacological therapies, and psychological therapies in IBS. We considered RCTs comparing pharmacological therapies with placebo, psychological therapies with either no treatment or standard/usual care or dietary therapies with standard dietary advice, habitual diet or a sham dietary therapy.…”
Section: Methodology For Systematic Reviews Of Ibs Therapymentioning
confidence: 99%
“…We considered the following treatments: soluble or insoluble fibre, a diet low in fermentable oligosaccharides, disaccharides and monosaccharides and polyols (FODMAPs), a gluten-free diet, probiotics, antidiarrhoeals, antispasmodic drugs (including peppermint oil), laxatives, gut-brain neuromodulators (tricyclic antidepressants (TCAs) and SSRIs, previously termed antidepressant drugs), eluxadoline, 5-HT 3 receptor antagonists, antibiotics, secretagogues, 5-HT 4 receptor agonists or psychological therapies (including gut-directed hypnotherapy) (online supplemental table 1). As this was an update of prior meta-analyses, [153][154][155][156][157][158][159][160][161][162][163]…”
Section: Methodology For Systematic Reviews Of Ibs Therapymentioning
confidence: 99%
“…abdominal pain) were not assessed. Other carefully conducted reviews including network meta-analyses have reported benefit with psychological therapies in IBS, but the majority of included studies had no placebo or sham comparison leading to concerns for possible overestimation of treatment effects 7,8 . Meanwhile, a 2016 systematic review and meta-analysis 9 of randomized controlled trials (RCTs) of Chinese herbal medicine for diarrhea-predominant IBS found significant improvement in overall symptoms, diarrhea, and abdominal pain, but was restricted by small patient numbers and a limited bias assessment.…”
Section: Introductionmentioning
confidence: 99%